NUTRITIONAL EVALUATION OF FEW SELECTED MEDICINAL PLANTS OF NORTH EASTERN REGION - CHANDANA C BARUA; MONDIRA BORA; BIBEKA N SAIKIA; MINESWAR HAZARIKA; JYOTI MISRI; ISWAR CHANDRABARUA (International Journal of Pharma and Bio Sciences, 2015)
Six Medicinal plants species viz. Homalomena aromatica, Clerodendrum indicum, Elsholtzia communis, Zanthoxylum alatum, Drymaria cordata and Gnetum gnemon of the North Eastern region of India were estimated for their proximate composition and minerals content on dry matter basis. The crude protein content of different plant species in descending order were Drymaria cordata (20.57%) followed by Homalomena aromatica (20.5%), Elsholtzia communis (16.19%), Zanthoxylum alatum (10.94%), Clerodendrum indicum (7.88%) and Gnetum gnemon (6.7%). The crude fat content ranged from 0.31%-1.27% and crude fibre 7.31%-20.0% in different plant species. These plants/herbs were also rich in mineral content. While the Moisture content was highest in Clerodendrum indicum (15.4%)and Carbohydrate content was in Gnetum gnemon (65.61%). Among the trace element constituents iron was found to be the highest (10 to 792ppm) followed by Zinc(0.65-6.72ppm) and Copper(0.01-1ppm). However the percentage of calcium and phosphorus were found to be optimum level in comparison to other conventional plant species. The study revealed the fact that these six wild edible plants species could be used as a nutritional supplement.